"Dangerous Government": Info-Liberalism, Active Citizenship, and the Open Government Directive. (April 2014) - Catlaw, Thomas J.; Sandberg, Billie
There has been much debate about the change Barack Obama represents. This article considers this question by using Michel Foucault's concept of governmentality to explore the underlying governmental rationality of his administration's policies and management practices. Obama's governmentality is examined via the Open Government Directive, arguably the central initiative of the administration. The article concludes that this governmentality may be viewed as a mutation within neoliberalism, which the authors call info-liberalism —one that deploys a novel, integrative conception of social government. Info-liberalism is examined in conjunction with the contemporary usage of the term governance to analyze more broadly the dynamics of government and citizen participation today.